2004
DOI: 10.1007/s00414-004-0481-0
|View full text |Cite
|
Sign up to set email alerts
|

Serial monitoring of interleukin-1?, soluble interleukin-2 receptor and lipopolysaccharide binding protein levels after death

Abstract: We prospectively monitored the postmortem course of interleukin-1beta (IL-1beta), soluble interleukin-2 receptor (sIL-2R) and lipopolysaccharide binding protein (LBP) in septic and non-septic fatalities to evaluate their potential as biochemical postmortem markers of sepsis. Serum concentrations were determined by chemiluminescent immunometric assays. In both the sepsis group and the control group a postmortem increase of IL-1beta levels with the progression of time after death was observed, in both groups mai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 27 publications
(43 reference statements)
0
26
0
2
Order By: Relevance
“…The acutephase protein LBP is a 60-kDa serum glycosylated protein, forming high-affinity complexes with bacterial endotoxins (lipopolysaccharide), functioning as an opsonin, that is produced and secreted by hepatocytes. The reference limit of LBP in healthy individuals is less than 10 μg/ml [83][84][85]. The results of this study showed increased sIL-2R and LBP postmortem serum levels over the clinical reference limits in sepsis-related fatalities, suggesting that these markers could be an appropriate diagnostic tool, in combination with other biochemical markers, in the postmortem diagnosis of sepsis in forensic autopsy practice.…”
Section: Acute-phase Proteins and Cytokinesmentioning
confidence: 56%
See 1 more Smart Citation
“…The acutephase protein LBP is a 60-kDa serum glycosylated protein, forming high-affinity complexes with bacterial endotoxins (lipopolysaccharide), functioning as an opsonin, that is produced and secreted by hepatocytes. The reference limit of LBP in healthy individuals is less than 10 μg/ml [83][84][85]. The results of this study showed increased sIL-2R and LBP postmortem serum levels over the clinical reference limits in sepsis-related fatalities, suggesting that these markers could be an appropriate diagnostic tool, in combination with other biochemical markers, in the postmortem diagnosis of sepsis in forensic autopsy practice.…”
Section: Acute-phase Proteins and Cytokinesmentioning
confidence: 56%
“…Reichelt et al [83] investigated interleukin-1β (IL-1β), soluble interleukin-2 receptor (sIL-2R) and lipopolisaccharide binding protein (LBP) in postmortem serum from femoral blood in two series of autopsy cases (eight septic cases and 16 control cases). IL-1β is predominantly produced by monocytes/macrophages as an inactive 31 kDa precursor protein (pIL-1β) and is processed to its active 17.5 kDa form by the specific interleukin-1β converting enzyme.…”
Section: Acute-phase Proteins and Cytokinesmentioning
confidence: 99%
“…There are also studies indicating that assays of soluble IL-2 receptor (sIL-2R) -a marker Archiwum Medycyny Sądowej i Kryminologii Archives of Forensic Medicine and Criminology tora interleukiny 2 (sIL-2R) -markera aktywacji limfocytów, endokanu (ESM1) -markera dysfunkcji śródbłonka naczyniowego [9,10]. W diagnostyce pośmiertnej inwazyjnych zakażeń grzybiczych, któ-re dotyczą głównie osób z nabytymi lub wrodzonymi niedoborami odporności, wykazano efektywność oceny stężenia β-glukanu w surowicy lub innych płynach ustrojowych [11].…”
Section: Archiwum Medycyny Sądowej I Kryminologii Archives Of Forensiunclassified
“…Należy ich szukać zarówno na skórze, jak i błonach śluzowych. Z kolei w zespole toksycznej nekrolizy naskórka (TEN) i gronkowcowego złuszczającego zapalenia skóry (SSSS) domiof lymphocyte activation, and endocan (ESM1) -a marker of vascular endothelial dysfunction could also be used for that purpose [9,10]. An assessment of β-glucan concentration in the blood serum or other bodily fluids has also been demonstrated to be an effective test in the post-mortem diagnostics of invasive fungal infections occurring mainly in patients with congenital or acquired immunodeficiencies [11].…”
Section: Sekcja Zwłokmentioning
confidence: 99%
“…Furthermore, postmortem cytokine levels in systemic inflammation have been studied extensively by other researchers [13,14]. However, these studies discussed the association between postmortem cytokine levels and sepsis.…”
Section: Introductionmentioning
confidence: 97%